Social Anarchism and the Rejection of Moral Tyranny - Spafford, Jesse (Cambridge University Press, 2023)
This book aims to provide a philosophical defense of egalitarian anarchism, more popularly known as social anarchism. It is certainly not the first book to attempt to defend this position; numerous egalitarian anarchists across time and place have already produced something of a canon of works expounding and arguing for the ideology. However, this book stands apart from these prior efforts in that it employs the tools of contemporary analytic philosophy to construct its argument. While popular defenses of anarchism generally seek to persuade through the use of rhetoric and informal argumentation, this book aspires to provide something closer to a proof of its thesis, with heavy reliance on logic, the precise definition of terms, and concepts developed by academic philosophers